J.-F. Lyotard: the Role of Science in Postmodern Society - Gedutis, Aldis (Problemos, 2002)
The article discusses Jean-Fran
Keywords: Lyotard; Habermas; science; politics; performativity; paralogy; concensus; metanarratives